PARISH RENEWAL: A CATHOLIC CHARISMATIC RENEWAL APPROACH - Simanullang, Gonti (LOGOS, 2013)
Parish renewal is about renewal of the faith and life of the faithful in the parish. It implies that every single member of the parish, due to the sacrament of initiation received, is called to live out their faith. In reality, however, not every one of the faithful is concernedabout the renewal. There are Catholics who are not practicing their faith anymore, not going to church on Sundays and the days of obligation. The Catholic Charismatic Renewal (CCR),as one of the ecclesial movements recognized within the Catholic Church, seems to have got something to offer for such a renewal, that is their personal experience of being touched, renewed, and strengthened by the Holy Spirit.